2010
DOI: 10.3765/exabs.v0i0.532
|View full text |Cite
|
Sign up to set email alerts
|

What Errors Can’t Tell Us About Heritage Grammars: On Covert Restructuring of Aspect in Russian

Abstract: The paper examines covert restructuring of the aspectual system of Russian in the context of heritage acquisition, i.e. systematic grammatical reorganization not manifested in overt errors. The interaction between VP-level aspectuality and sentential aspect is examined in the data from high-proficiency heritage speakers and baseline speakers of Russian. While the two grammars largely converge at the VP level (particularly in atelic contexts), they differ with respect to how sentential aspect is expressed, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
1
12
0
1
Order By: Relevance
“…In fact, masculine and singular forms seem to predominate over plural and feminine forms in the two domains. The fact that heritage speakers over-generalize the masculine singular category is consistent with data from other heritage populations suggesting that masculine and singular are less marked in the acquisition of inflectional morphology (Albirini et al, 2011; Cornips & Hulk, 2006; Laleko, 2010; Montrul, 2008; Montrul et al, 2008; Polinsky, 1997; Suh, 2008). This is most likely because the third masculine form is the simplest form within the paradigms in that it does not carry any phonologically overt agreement marker.…”
Section: Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…In fact, masculine and singular forms seem to predominate over plural and feminine forms in the two domains. The fact that heritage speakers over-generalize the masculine singular category is consistent with data from other heritage populations suggesting that masculine and singular are less marked in the acquisition of inflectional morphology (Albirini et al, 2011; Cornips & Hulk, 2006; Laleko, 2010; Montrul, 2008; Montrul et al, 2008; Polinsky, 1997; Suh, 2008). This is most likely because the third masculine form is the simplest form within the paradigms in that it does not carry any phonologically overt agreement marker.…”
Section: Methodssupporting
confidence: 79%
“…As we noted above, the third masculine form in Arabic is the simplest form within the paradigms in that it involves deploying the bare form of the adjective or verb. The over-generalization of default form shows that the relationship between L2 and L1 in L2 acquisition may have some resemblances to its counterpart in HLA, as has also been attested in a number of studies (e.g., Albirini et al, 2011; Alhawary, 2009; Cornips & Hulk, 2006; Laleko, 2010; Montrul et al, 2008; Polinsky, 1997; Suh, 2008). However, we believe that an independent study involving more than morphological area and perhaps multiple languages may be needed to ascertain the nature of these resemblances.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For instance, Hebrew-dominant speakers of heritage English do not make errors in the production or comprehension of English determiners despite the differences in the determiner systems of the two languages (Polinsky, 2018b; Viswanath, 2013). In the verbal domain, the headline is often that heritage speakers struggle with aspectual morphology; by comparison, difficulty with tense is seldom attested (see Montrul, 2016; Silva-Corvalán, 1994, and further references therein on aspect in heritage Spanish; Laleko, 2010, on aspect in heritage Russian; Jia & Bayley, 2008, on aspect in heritage Mandarin; Albirini, Benmamoun & Saadah, 2011, on aspect in heritage Arabic; Sherkina-Lieber, 2011, 2015, on tense vs. aspect in heritage Inuttitut). What do these phenomena have in common?…”
Section: Some Empirical Observationsmentioning
confidence: 99%
“…For example, unlike their monolingual counterparts, heritage speakers often display a relatively better command of phonological and syntactic aspects of their heritage languages than of lexical, morphological, and morphosyntactic areas (Bar-Shalom & Zaretsky, 2008; Montrul, 2004; Silva-Corvalán, 1994, 2003; Sorace, 2000; Tsimpli & Sorace, 2006). Likewise, it has been reported that, even within a single linguistic area, they are often more accurate in deploying unmarked forms than in using marked categories (Albirini, Benmamoun & Saadah, 2011; Cornips & Hulk, 2006; Laleko, 2010; Polinsky, 1997; Suh, 2008). These asymmetries have generated considerable interest in understanding the properties of heritage grammars that are prone to incomplete acquisition or attrition/loss as well as the underlying causes of their non-convergent acquisition or retention patterns.…”
Section: Introductionmentioning
confidence: 99%